2022
DOI: 10.3390/brainsci12121666
|View full text |Cite
|
Sign up to set email alerts
|

Converging Evidence Points to BDNF as Biomarker of Depressive Symptoms in Schizophrenia-Spectrum Disorders

Abstract: Brain-derived neurotrophic factor (BDNF) is a key modulator of neuroplasticity and has an important role in determining the susceptibility to severe psychiatric disorder with a significant neurodevelopmental component such as major psychoses. Indeed, a potential association between BDNF serum levels and schizophrenia (SCZ) and schizoaffective disorder (SAD) has been tested in diverse studies and a considerable amount of them found reduced BDNF levels in these disorders. Here, we aimed at testing the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…Recent studies on patients affected by schizophrenia have also detected a decrease in BDNF levels in CNS and peripheral serum samples. Accordingly, similar data were observed in several animal models of other neuropsychiatric disorders, such as anxiety and memory impairment [ 16 ]. Notably, acute and chronic social stress has been related to an alteration in NTs levels such as NGF and BDNF in humans and animals [ 41 ].…”
Section: Neurotrophins and Brainsupporting
confidence: 79%
See 2 more Smart Citations
“…Recent studies on patients affected by schizophrenia have also detected a decrease in BDNF levels in CNS and peripheral serum samples. Accordingly, similar data were observed in several animal models of other neuropsychiatric disorders, such as anxiety and memory impairment [ 16 ]. Notably, acute and chronic social stress has been related to an alteration in NTs levels such as NGF and BDNF in humans and animals [ 41 ].…”
Section: Neurotrophins and Brainsupporting
confidence: 79%
“…The alteration in its expression has been linked to neurodevelopmental disorders with an early onset and severe clinical manifestations, often named “synaptopathies” because of structural and functional synaptic plasticity abnormalities [ 38 , 88 , 89 ]. A reduction in BDNF levels has been demonstrated in neonatal blood samples of autistic subjects and in numerous animal models of autism and genetic syndromes related to autistic behaviours (e.g., Rett syndrome), but also in patients affected by schizophrenia and depression [ 6 , 16 , 33 , 34 , 38 , 90 ]. On the contrary, increased BDNF levels have been detected in the blood of patients affected by intellectual disability (ID) [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is a severe neuropsychiatric disorder associated with gradual impairment in multiple domains of functioning. 22 Its neurodevelopmental component appears prominent, and although the first episode of psychosis is generally observed in late adolescence or early adulthood, it is often preceded by prodromal symptoms that include nonspecific changes in mood and behavior 23 , social withdrawal, and cognitive symptoms. 24 Neuroinflammation may be a key player in the pathophysiology of SCZ.…”
Section: Introductionmentioning
confidence: 99%
“…Manchia et al aimed to evaluate the relationship between BDNF serum levels and several demographic, clinical, and psychometric measures in 105 patients with schizophrenia and schizoaffective disorder and assessed the moderating effect of genetic variants within the BDNF gene. This study revealed that BDNF serum levels are significantly lower in patients affected by schizophrenia and schizoaffective disorders presenting more severe depressive symptomatology [ 9 ].…”
mentioning
confidence: 99%